Waktu Henti Antibotik Chloramphenicol Terhadap Perubahan Kadar Residu Pada Ikan Bandeng (Chanos Chanos) - Didik Budiyanto; Sri Oetami Madyowati; Achmad Kusyairi (Rekayasa, 2022)
Milkfish is one of the fishery commodities that are in great demand by the Indonesian people, where the obstacle to production decline is disease. Therefore, to prevent disease and treat diseases that attack fish, farmers use the antibiotic Chloramphenicol. However, the use of high doses of antibiotics will cause resistance to pathogenic bacteria and the residue left in the fish's body will have a negative impact on human health who consume them such as allergies, toxicity and even cause death in anemia sufferers which can progress to leukemia. This study aims to determine the length of downtime of the antibiotic Chloramphenicol on changes in residual levels in milkfish (Chanos chanos) aged 30 days decreased to a safe limit for consumption. Residual content test using ELISA at 450 nm wave. Based on the results of the study, milkfish fed with a mixture of chloramphenicol antibiotics at a dose of 1 ppm resulted in the highest residual value of 4.6375 ppb in the first week and a decrease in residue to 0.2363 ppb for 5 weeks. The stopping time of chloramphenicol antibiotics on changes in residual levels in milkfish (Chanos chanos) aged 30 days in treatment F (Milkfish fed with a mixture of chloramphenicol at a dose of 1g/kg of feed for a week, then fed without a mixture of chloramphenicol for 5 weeks) resulted in a safe limit for consumption.